Alternative Energy for Energy Sustainability - Prasad, B.G Shiva; Sharma, Kal Renganathan (Annals of Arid Zone, 2016)
Energy has become a part and parcel of human survival and societal progress. In fact, per capita energy consumption has become a measure of a nation's progress. Just as air, water and food are the most important materials required for the survival of human life on earth, energy is essential for sustenance of the human race. Fear of depletion of fossil fuels, the main source of energy until now, has invigorated research for finding alternate sources. At the same. time, fear of climate change and global warming is attracting attention of scientists to cleaner sources of energy. This paper presents a discussion of the various sources, the status of technology and their merits and demerits for application to daily life. The present day popular sources like solar, wind, biomass and geothermal are discussed in greater detail. The authors also present arguments to dub geothermal as the best renewable and clean energy source. Key words: Solar energy, wind energy, geothe.mal energy, biofuels.